2017
DOI: 10.1039/c7fo00143f
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fatty acids on aortic root calcification in mice with metabolic syndrome

Abstract: This is the peer reviewed version of the following article: Dietary fatty acids on aortic root calcification in mice with metabolic syndrome. Food Funct., 2017, 8, 1468-1474 DOI: 10.1039

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, several nuts and fruits are sources of ω-9 fatty acids. It is also known that consumption of a diet rich in ω-9 fatty (3–23% dietary intake) acids exerts positive effects on the reduction of adiposity and cardiovascular risk as well as improvement of serum parameters—such as HDL-c and the LDL-c/HDL-c ratio [41,42,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…However, several nuts and fruits are sources of ω-9 fatty acids. It is also known that consumption of a diet rich in ω-9 fatty (3–23% dietary intake) acids exerts positive effects on the reduction of adiposity and cardiovascular risk as well as improvement of serum parameters—such as HDL-c and the LDL-c/HDL-c ratio [41,42,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to determine whether the LPH was able to restore the altered lipid profile by the WD; for this motif, the SD group was necessary only to confirm that the WD ingestion induces an alteration of this profile, according to other study designs. 25,[38][39][40][41][42][43] At the end of the experiment, fasted mice were euthanized by an overdose intraperitoneal injection, set for each mouse, of sodium thiopental (50 mg kg −1 , B. Braun Medical SA, Barcelona, Spain) that was effective within 1 min, and the liver was subsequently collected, rapidly frozen, and stored at −80 °C until use. Plasma and hepatic lipid profile parameters were quantified as described in the ESI.…”
Section: In Vivo Study Designmentioning
confidence: 99%
“…Fonolla‐Joya and colleagues revealed that administration of n ‐3 PUFAs led to decreased RANKL serum levels in postmenopausal women with moderate cardiovascular risk . Naranjo et al showed that in comparison with dietary MUFAs (from olive oil) prevented atherosclerosis by getting involved in vascular calcification and the use of RANKL/RANK/OPG system in the setting of metabolic syndrome …”
Section: Fatty Acid and Opg/rankl/rank System In Cvdmentioning
confidence: 99%
“…79 Naranjo et al showed that in comparison with dietary MUFAs (from olive oil) prevented atherosclerosis by getting involved in vascular calcification and the use of RANKL/RANK/OPG system in the setting of metabolic syndrome. 80…”
Section: Fatty Acid and Opg/rankl/rank System In Cvdmentioning
confidence: 99%